Covid-19 pandemic: The All India Occupational Therapists' Association's response to the challenges. Issue 2 (2nd July 2020) - Srivastava, Anil K.; Mishra, Neeraj; Sethuraman, Lakshmanan
ABSTRACT: COVID-19 Pandemic has caused severe disruption in all spheres of life of common man across the globe. The All India Occupational Therapists' Association has taken initiatives to combat the issues emerging in the times of pandemic by empowering the occupational therapy professionals across the country, which in turn may help the individuals to get back to the new normal life situations. The initiatives also focused on plans for occupational therapy schools to continue enriching students with the knowledge and partnering with other stakeholders to minimise the impact of this disease. The initiatives undertaken by AIOTA are well appreciated by the Ministry of Health, Government of India, World Federation of Occupational Therapists (WFOT), occupational therapy educational institutions and occupational therapy professionals across the country and also overseas.